Emerging Importance of Chemokine Receptor CXCR4 and Its Ligand in Liver Disease - Wang, Sheng; Gao, Songsen; Li, Yueran; Qian, Xueyi; Luan, Jiajie; Lv, Xiongwen (Frontiers in Cell and Developmental Biology, 2021)
Chemokine receptors are members of the G protein-coupled receptor superfamily, which together with chemokine ligands form chemokine networks to regulate a variety of cellular, physiological, and immune processes. These receptors are intimately involved in cell movement, and thus play a critical role in several physiological and pathological situations that require regulation of cell migration. CXCR4 is one of the most studied chemokine receptors and is involved in many functions beyond immune cells recruitment and plays a pivotal role in the pathogenesis of liver disease. Aberrant CXCR4 expression pattern is related to the migration and movement of liver specific cells in liver disease through its cross talk with various important cell signaling pathways. A deeper insight into understanding of CXCR4 mediated signaling pathways and its role in liver disease is essential to identify potential therapeutic interventions. Current therapeutic strategies for liver disease mainly focus on regulating the key functions of specific cells in the liver, in which the CXCR4 pathway plays a vital role. There are still multiple challenges that need to be overcome to target CXCR4 pathway more efficiently and to identify novel combination therapies with existing strategies. This review highlights the role of CXCR4 and its significant cell signaling pathways in the pathogenesis of liver disease and summarizes the targeted therapeutic studies conducted to date.